SOBRASA Statements: Individual Athlete´s Checklist to Reduce Adverse Events in Open Water - Szpilman, David (2020)
Introduction: In 1988, the Brazilian Renata Agondi, 25 years old, died while crossing the English Channel. In 2010, American Franz Cripen, vice-champion of world aquatic marathon, died during an open water swimming event. Such fatalities provoked changes in the safety of evidence in open waters, but still with unsatisfactory results. In recent years, there has been an increase in the number of incidents and deaths in training and competitions. Objective: To present the pre-participation evaluation instrument in a sporting event in open waters of the Brazilian Rescue Society (Sociedade Brasileira de Salvamento: SOBRASA). It is a self-questionnaire in “checklist” format with simple answers’ options (Yes/No), which allows the athlete to evaluate, before participation, the safety of the event. Conclusion: To develop the questionnaire, a focus group was formed consisting of 16 specialists (health and sports professionals, military firefighters and athletes from open water events) who sought to list and discuss the variables involved in holding a swimming in open water event, and additionally to identify ways to reduce them. In despite of all the safety precautions observed in this type of event, there is no possibility to guarantee 100% protection. In this context, it is up to the organizers and the athlete / competitor to carefully consider the risks involved in participating in the event, seeking to reduce them in order to avoid undesirable incidents. [Full text in English available]